Developing Professional Identity and Ethos through Research and Practice in Initial Teacher Education: The USW ITE Partnership Approach. (1st March 2020) - Daly, Caroline; James, Jamie; Jones, Catherine; Taylor, Lisa; Wegener, Kelly; George, Craig
Reform of the education sector in Wales has given university-school partnerships of Initial Teacher Education (ITE) in Wales much to grapple with conceptually and practically, in order to design new programmes of ITE that can attract national-level accreditation in line with the recommendations made by Professor John Furlong in 2015. These reforms have required a system-wide rethink of ITE, based on a philosophy for new provision. This article outlines an approach to ITE inspired by the work of Lee Shulman (2005) who argued that teacher education should prioritise the acquisition of three habits, corresponding to the 'what' the 'so what' and finally the 'who' of teaching, namely an understanding of one's professional identity, ethos and character. We describe a pedagogical model for embedding these principles in ITE, based on the work of Parker, Patton and O'Sullivan (2016). Finally, we consider the implications for mentors and lecturers, noting in particular the need to see all members of the ITE partnership as learners, both to ensure effective role models for beginning teachers, and also to remain faithful to the principle laid down in social development theory (Vygotsky, 1978) that learning is interactive and symbiotic.